Coherence in the argumentative essays of ADZU college freshmen: A textual analysis of writing quality - Angeles, Mary Sheildred Duterte (Animo Repository, 2005)
The present study investigated five textual features of coherence in the students’ argumentative essays for text comprehensibility and overall writing quality. Specifically, it examined (1) how textual features such as Focus, Organization, Cohesion, Support and Elaboration, and Conventions were achieved in the students’ argumentative essays to make them comprehensible; (2) how comprehensible the students’ argumentative essays considering the following: (a) Focus,(b) Organization, (c) Cohesion, (d) Support and Elaboration, and (e) Conventions; and (3) the relationship between the textual features and the comprehensibility of the students’ argumentative essays and between the comprehensibility of the students’ argumentative essays and the type of high school (private or public) attended. The data consisted of 30 argumentative essays written in English 112 class by regular first year college students of Ateneo de Zamboanga University. Three techniques were used to analyze the data. First, a textual analysis involving frequency count was conducted to identify the different characteristics of the coherence features in the students’ texts. Second, analytic and holistic scorings using a four-point writing rubric were used to evaluate each of the textual features of coherence and comprehensibility, respectively. Third, correlational analysis was performed to determine the relationship between the coherence features and the comprehensibility of the students’ texts and between the comprehensibility of the students’ argumentative essays and the type of high school the students attended. The findings indicate that the students’ argumentative essays that were considered comprehensible employed different characteristics of good writing and that they were mostly rated as moderately comprehensible based on their obtained mean score points. The results further reveal that the textual features of coherence showed significant positive correlations with comprehensibility although with varying degrees of relationship. Of the five features, Conventions received the highest correlation with comprehensibility, whereas Cohesion had the lowest. On the other hand, the comprehensibility of the students’ argumentative essays did not show any significant relationship with the type of high school (private or public) students attended.